Evaluation of melatonin levels in saliva in gingivitis and periodontitis cases: A pilot study - Karuna Lodhi; Charanjit Singh Saimbi; Mohammad Akhlaq Khan; Chandishwar Nath; Rakesh Shukla (Wolters Kluwer Medknow Publications, 2016)
Objective: To evaluate the melatonin levels in saliva in gingivitis and periodontitis cases. Background: Melatonin has strong antioxidant, free radical scavenging, and immunomodulating properties, acts on osteoblasts directly to stimulate cell proliferation and synthesis of Type I collagen, and promotes bone formation. Materials and Methods: A total of thirty participants were selected and divided into three groups (control group, gingivitis group, and periodontitis group). In each group, ten participants were taken. Salivary melatonin was estimated in each of the three groups. Results: Results from this study showed that the mean levels of salivary melatonin increased as severity increased from control to periodontitis, i.e., the mean levels were highest in periodontitis followed by gingivitis and least in control group. The melatonin level of all participants was positively and significantly (P < 0.01) correlated with their gingival index (r = 0.85, P< 0.01) and probing depth (r = 0.72, P< 0.01). Conclusion: Salivary melatonin level varied with the severity of gingivitis and periodontitis. With increased severity of periodontal disease, the level of salivary melatonin also increased suggesting that salivary melatonin may act as a diagnostic biomarker for periodontal diseases.